Mineralogical characterization of oresamples of different pH in the Björkdal golddeposit, northern Sweden – implications formineral processing - Ekholm, Niklas (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2021)
The Björkdal gold deposit is situated in the Skellefte mining district, northern Sweden. The ore is mined from a complex system of quartz veins ranging from a few cm to a meter in width. The mineral processing steps at Björkdal comprises a flotation circuit, which performance is dependent on the pH of the ore feed. A total of ten samples from five different ore zones from the underground development was investigated with the purpose of improving the understanding of factors that causes the pH value of rock samples to vary which is deleterious to the metal recovery. The samples were investigated with optical microscopy together with scanning electron microscopy (SEM) and automated mineralogy (QEMSCAN) to carry out the modal mineralogy. The analyses identified a total of 37 different minerals in the samples. Chlorite was identified with significantly higher values in parts of the investigated ore zones and especially in the sample with the highest pH value, suggesting chlorite-hosting shear zones that crosscut the sampled ore zones to be a contributing factor that could be affecting the elevated pH values, resulting in a decreased recovery of gold.